Skill Training Periodization in “Specialist” Sports Coaching—An Introduction of the “PoST” Framework for Skill Development - Otte, Fabian W.; Millar, Sarah-Kate; Klatt, Stefanie (Frontiers in Sports and Active Living, 2019)
Across sports and movement science, training periodization has been recognized as key for athlete development and performance. While periodization with regard to physiology has a proven history, the structuring and periodization of motor learning and skill development is seemingly less researched and practiced. Despite the existence of numerous theoretical accounts underpinning skill acquisition training and more recently emerging periodization models, a cohesive framework to practically support coaches in the context of “specialist coaching” appears to be needed. The use of “specialist coaches” for individualized, one-on-one or small group trainings displays a growing trend in team ball sports. Despite limiting the replication of game-representative environments (i.e., by constraining the number of involved athletes in training), “specialist coaches” in performance sport constantly aim to achieve marginal gains and refinements in athlete development. In order to support these “specialist coaches” and fill a research gap on skill training periodization, the current paper seeks to review and transfer contemporary skill acquisition training theory (driven by the constraints-led approach) into a practically-applicable “Periodization of Skill Training” framework (“PoST” framework). This framework provides valuable conceptual and practical support for “specialist coaches” in performance sport; which will in turn, enhance, and refine adaptive movement variability for sport skills and manipulate skill training environments (i.e., over the course of macro- and micro-cycles, and for the planning of single training sessions). Practical examples from soccer goalkeeping (i.e., a “specialist coaching” context, often constrained to a small number of players in the training environment) will underline the proposed framework.